Human Rights Norms: Between Principles and Rules - Rabanos, Julieta (Iuris Dictio, 2021)
On the occasion of the 70th anniversary of the Universal Declaration of Human Rights (UDHR), I propose to reflect about the conceptual problem regarding the normative texts or sentences that are used to recognise and/or establish human rights. The question can be put in these terms: what kind of norms do these normative texts or sentences express? Are they rules, principles, or both, depending on the circumstances? Answering this question involves the solution of two distinct problems. On the one hand, a conceptual problem: what kind of theory or approach can give better account of human rights norms? On the other hand, an axiological problem: how should we consider human right norms, according a given (best, correct) doctrine or ideology? In this article, I try to explore and offer some answers to this main question and its connected problems.